Secure Precoding Design for RSMA Transmission in HAP-Assisted Non-Terrestrial Networks - Huang, Mengyan; Gong, Fengkui; Zhao, Jiahui; Yin, Zhisheng; Li, Xingwang; Pham, Quoc-Viet (IEEE transactions on vehicular technology, 2025)
The non-terrestrial networks (NTNs) are recognized as a key component to provide cost-effective and high-capacity ubiquitous connectivity in the future wireless communications. To improve the spectral efficiency in NTNs, rate-splitting multiple access (RSMA) has attracted considerable attention. Nevertheless, the major issue of the considered system is to overcome security hurdles. In this paper, a robust secure precoding transmission scheme based on RSMA is proposed, which is the first time being used for high-altitude platform (HAP)-assisted satellite NTNs. The system features a low-Earth orbit satellite that serves multiple ground user equipments (GUEs) using a rate-splitting strategy, while a decode-and-forward HAP relay assists the satellite in establishing communication links with the GUEs. Assuming imperfect channel state information, we formulate an optimization problem to maximize the sum secrecy rate (SSR) of GUEs. The problem jointly optimizes the precoding vectors for both the satellite and the HAP relay, subject to constraints on their maximum transmit powers and the achievable secrecy rates for each GUE. Subsequently, leveraging successive convex approximation and semidefinite relaxation, we present an approach to transform the non-convex constraints into convex ones, enabling the precoding vectors to be obtained through an iterative procedure. Simulation results show that the RSMA can achieve SSR of up to 3.25 bps/Hz and 3.75 bps/Hz compared to non-orthogonal multiple access and time division multiple access, respectively.